The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.3389/fams.2019.00009
|View full text |Cite
|
Sign up to set email alerts
|

Cloning of Chimera States in a Large Short-term Coupled Multiplex Network of Relaxation Oscillators

Abstract: A new phenomenon of the chimera states cloning in a large two-layer multiplex network with short-term couplings has been discovered and studied. For certain values of strength and time of multiplex interaction, in the initially disordered layer, a state of chimera is formed with the same characteristics (the same average frequency and amplitude distributions in coherent and incoherent parts, as well as an identical phase distribution in coherent part), as in the chimera which was set in the other layer. The me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 45 publications
0
3
0
2
Order By: Relevance
“…Recently, a prominent line of research emerged which studies chimera states in multilayer networks [42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57]. Multilayer networks are important modelling tools for complex systems such as transportation networks, social interactions and the brain [58,59].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, a prominent line of research emerged which studies chimera states in multilayer networks [42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57]. Multilayer networks are important modelling tools for complex systems such as transportation networks, social interactions and the brain [58,59].…”
Section: Introductionmentioning
confidence: 99%
“…In Ref. [56] the authors showed that it is possible to clone a chimera states from one layer to another of a multiplex network even when the coupling is active only for a short time. For a two-layer network of oscillatory FitzHugh-Nagumo units, a control strategy based on weak multiplexing was developed allowing to induce or suppress chimera states [52].…”
Section: Introductionmentioning
confidence: 99%
“…The observation of amplitude chimera states against the conventional phase chimera is also a notable advance in the field preceded by the identification of imperfect amplitude chimera due to attractive and repulsive interactions in a non-locally coupled Stuart Landau oscillators [17,18]. At the frontier one can see the extension of network topology to multilayer and multiplex networks for understanding chimera states [19][20][21]. Practical application of chimera states are demonstrated in the laboratory in the last decade apart from the theoretical and numerical analysis [22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…Эти эффекты типичны для биологических объектов и нейронных сетей мозга [16,17]. Недавно [18,19] был обнаружен и изучен новый эффект -клонирование химерных состояний, возникающий при объединении в мультиплексную систему двух кольцевых ансамблей линейно локально связанных бистабильных осцилляторов. Численно было показано, что при определенных зна-чениях силы и времени межкольцевого взаимодействия в кольце с изначально беспорядочным распределением фаз формируется копия химерного состояния, наблюдаемого в другом кольце, с точностью до значений фаз в некогерентной части.…”
unclassified
“…Численно было показано, что при определенных зна-чениях силы и времени межкольцевого взаимодействия в кольце с изначально беспорядочным распределением фаз формируется копия химерного состояния, наблюдаемого в другом кольце, с точностью до значений фаз в некогерентной части. В основе эффекта лежит конкурентная динамика пар осцилляторов из разных слоев мультиплексной системы [18,19].…”
unclassified